Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) Lm r nkoa!
b) \(\left(0,25x\right):3=\frac{5}{6}:0,125\)
\(=\left(0,25x\right):3=\frac{20}{3}\)
\(\Rightarrow0,25x=\frac{20}{3}\cdot3=20\)
\(\Rightarrow x=20:0,25=80\)
\(\Rightarrow x=80\)
c) \(0,01:2,5=\left(0,75x\right):0,75\)
\(=\frac{1}{250}=\left(0,75x\right):0,75\)
\(\Rightarrow0,75x=\frac{1}{250}\cdot0,75=\frac{3}{1000}\)
\(\Rightarrow x=\frac{3}{1000}:0,75=\frac{1}{250}\)
\(\Rightarrow x=\frac{1}{250}\)
d) \(1\frac{1}{3}:0,8=\frac{2}{3}:\left(0,1x\right)\)
\(=\frac{5}{3}=\frac{2}{3}:\left(0,1x\right)\)
\(\Rightarrow0,1x=\frac{2}{3}:\frac{5}{3}=\frac{2}{5}\)
\(\Rightarrow x=\frac{2}{5}:0,1=4\)
\(\Rightarrow4\)
C = \(25.\left(\frac{-1}{3}\right)^3\) \(+\frac{1}{5}\) \(-2.\left(\frac{-1}{2}\right)^2\) \(-\frac{1}{2}\)
C = \(25.\left(\frac{-1}{27}\right)+\frac{1}{5}\) \(-2.\frac{1}{4}\) \(-\frac{1}{2}\)
C = \(\frac{-25}{27}\) \(+\frac{1}{5}\) \(-\frac{1}{2}\) \(-\frac{1}{2}\)
C = \(\frac{-25}{27}\) \(+\frac{1}{5}\) \(-1\)
C = \(\frac{-125}{135}\) \(+\frac{27}{135}\) \(-\frac{135}{135}\)
C = \(\frac{-233}{135}\)
D = \(-8.\left(\frac{3}{4}-\frac{1}{4}\right):\left(\frac{9}{4}-\frac{7}{6}\right)\)
D = \(-8.\frac{1}{2}\) \(.\frac{12}{13}\)
D = \(-4.\frac{12}{13}\)
D = \(\frac{-48}{13}\)
E = \(5\sqrt{16}\) \(-4\sqrt{9}\) \(+\sqrt{25}\) \(-0,3\sqrt{400}\)
E = \(5.4-4.3+5-0,3.20\)
E = \(20-12+5-6\)
E = \(8+\left(-1\right)\)
E = \(7\)
F = \(\left(\frac{-3}{2}\right)\) \(+\left|\frac{-5}{6}\right|\) \(-1\frac{1}{2}\) \(:6\)
F = \(\left(\frac{-3}{2}\right)\) \(+\frac{5}{6}\) \(-\frac{3}{2}\) \(.\frac{1}{6}\)
F = \(\left(\frac{-3}{2}\right)\) \(+\frac{5}{6}\) \(-\frac{1}{4}\)
F = \(\left(\frac{-18}{12}\right)\) \(+\frac{10}{12}\) \(-\frac{3}{12}\)
F = \(\frac{-11}{12}\)
Chúc cậu hk tốt ~
\(\left(3-\frac{1}{4}+\frac{2}{3}\right)-\left(5-\frac{1}{3}-\frac{6}{5}\right)-\left(6-\frac{7}{4}+\frac{3}{2}\right)\)
\(=3-\frac{1}{4}+\frac{2}{3}-5+\frac{1}{3}+\frac{6}{5}-6+\frac{7}{4}-\frac{3}{2}\)
\(=\left(3-5-6\right)+\left(\frac{-1}{4}+\frac{7}{4}-\frac{3}{2}\right)+\left(\frac{2}{3}+\frac{1}{3}\right)+\frac{6}{5}\)
\(=-8+\left(\frac{3}{2}-\frac{3}{2}\right)+1+\frac{6}{5}\)
\(=-7+\frac{6}{5}\)
\(=\frac{-35}{5}+\frac{6}{5}=-\frac{29}{5}\)
7/4.x+3/2=-4/5
7/4.x=-4/5-3/2
7/4.x=-23/10
x=-23/10:7/4
x=-46/35
vậy x=-46/35
1/4+3/4.x=3/4
1.x=3/4
x=3/4:1
x=3/4
vậy x=3/4
x.(1/4+1/5)-(1/7+1/8)=0
x.9/20-15/56=0
x.51/280=0
x=0:51/280
x=0
vậy x=0
3/35-(3/5+x)=2/7
(3/5+x)=3/35-2/7
(3/35+x)=-1/5
x=-1/5-3/5
x=-4/5
vậy x=-4/5
\(a,1\frac{3}{4}.x+1\frac{1}{2}=\frac{4}{5}\)
\(\frac{7}{4}.x=\frac{4}{5}-\frac{3}{2}\)
\(\frac{7}{4}.x=\frac{-7}{10}\)
\(x=\frac{-7}{10}:\frac{7}{4}\)
\(x=\frac{-2}{5}\)
\(b,\frac{1}{4}+\frac{3}{4}.x=\frac{3}{4}\)
\(\frac{3}{4}.x=\frac{3}{4}-\frac{1}{4}\)
\(\frac{3}{4}.x=\frac{1}{2}\)
\(x=\frac{1}{2}:\frac{3}{4}\)
\(x=\frac{2}{3}\)
\(c,x.\left(\frac{1}{4}+\frac{1}{5}\right)-\left(\frac{1}{7}+\frac{1}{8}\right)=0\)
\(x.\frac{9}{20}-\frac{15}{56}=0\)
\(x.\frac{9}{20}=\frac{15}{56}\)
\(x=\frac{15}{56}:\frac{9}{20}\)
\(x=\frac{25}{42}\)
\(d,\frac{3}{35}-\left(\frac{3}{5}+x\right)=\frac{2}{7}\)
\(\frac{3}{5}+x=\frac{3}{35}-\frac{2}{7}\)
\(\frac{3}{5}+x=\frac{-1}{5}\)
\(x=\frac{-1}{5}-\frac{3}{5}\)
\(x=\frac{-4}{5}\)
Học tốt
\(A = {1\over2}-{3\over4}+{5\over6}-{7\over12}={6\over12}-{9\over12}+{10\over12}-{7\over12}\)\(={0\over12}=0\)
\(\left(1+\frac{2}{3}-\frac{1}{4}\right)\left(0.8-\frac{3}{4}\right)^2\)
= \(\left(\frac{12+8-3}{12}\right)\left(\frac{3,2-3}{4}\right)^2\)
= \(\frac{17}{12}.\left(\frac{0,2}{4}\right)^2\)
\(\frac{17}{12}.\frac{1}{400}\)
=\(\frac{17}{4800}\)
\(\left(1+\frac{2}{3}-\frac{1}{4}\right)\left(0,8-\frac{3}{4}\right)^2\)
\(=\left(\frac{12}{12}+\frac{8}{12}-\frac{3}{12}\right)\left(\frac{4}{5}-\frac{3}{4}\right)^2\)
\(=\frac{17}{12}\cdot\left(\frac{16}{20}-\frac{15}{20}\right)^2\)
\(=\frac{17}{12}\cdot\left(\frac{1}{20}\right)^2\)
\(=\frac{17}{12}\cdot\frac{1}{400}\)
\(=\frac{17}{4800}\)